A new Ateuchus guatemalensis (Bates, 1887) (Coleoptera: Scarabaeidae) synonym from Mexico - Kohlmann, Bert (Zootaxa, 2019)
This note reports on placement of Ateuchus benitojuarezi Moctezuma, Sánchez-Huerta, & Halffter, 2018 (Coleoptera: Scarabaeidae: Scarabaeinae: Ateuchini) as a junior synonym of Ateuchus guatemalensis (Bates, 1887) new synonymy. Ateuchus guatemalensis was originally described from Guatemala and is now known from Chiapas (Mexico), Honduras, and Nicaragua (Kohlmann & Vaz-de-Mello 2018). With the new synonym discussion below, A. guatemalensis also occurs in the Chimalapas region in Oaxaca (Mexico), thus following a very typical biogeographic distribution pattern known from other dung beetles that encompasses the Pacific slope between the Isthmus of Tehuantepec to the Nicaraguan lakes (Solís & Kohlmann 2012).